Long-term treatment of pulmonary arterial hypertension with macitentan in Japanese patients. (2nd June 2020) - Tahara, Nobuhiro; Dobashi, Hiroaki; Fukuda, Keiichi; Funauchi, Masanori; Hatano, Masaru; Ikeda, Satoshi; Joho, Shuji; Kihara, Yasuki; Kondo, Takahisa; Matsushita, Masakazu; Minamino, Tohru; Nakanishi, Norifumi; et al.
Abstract: Objective: Macitentan, a novel dual endothelin receptor antagonist, was approved for the treatment of pulmonary arterial hypertension (PAH) in Japan. However, long-term effects in Japanese patients of macitentan are currently unavailable. This study sought to assess the long-term efficacy and safety of macitentan in Japanese patients with PAH. Methods: In this multicenter, open-label, clinical extension study (JapicCTI-121986), efficacy was evaluated based on the change from baseline at 24, 48, 72, 96 and 120-week in the 6-minute walk distance (6MWD), World Health Organization (WHO) functional class, and serum N-terminal pro-brain natriuretic peptide (NT-pro-BNP) levels. In addition, the time to a hospitalization related to PAH and a morbidity/mortality event was determined. As for safety, the incidence of adverse events and changes in laboratory data and vital signs were assessed. Results: Macitentan was administered at a once-daily dose of 10 mg in 30 PAH patients with a median treatment period of 2.4 years (range, 229–1037 days). The improvements in 6MWD, WHO functional class and NT-pro-BNP at week 24 were maintained throughout the long-term follow-up. Hospitalization related to PAH occurred in 2 patients. Levels of liver enzyme and hemoglobin remained unchanged throughout the study period. Conclusions: This study suggests that the long-term use of macitentan is well tolerated and effective in Japanese patients with PAH. We concluded that macitentan can be a possible approach to reduce morbidity/mortality in Japanese PAH patients.